Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages 6 (b) Individuality, and Opportunity for its Expression. As society becomes more highly organized the danger of unnecessary restrictions increases and emphasizes the need for close scrutiny of any new scheme affecting society at large. It is particularly the mechanism by which the scheme may be administered that needs close scrutiny for this reason. For example, the unemployed may reasonably be expected to seek work where their service may be appropriate, but this in immature or "homefast" people leads to depression and other incapacitating disability which may defeat the very purposes of the transfer, especially if adequate measures for their re-settlement have not been taken at the place of transfer. The fullest exercise of individual choice in this matter needs safeguarding, and in exceptional circumstances it might even in the long run be better to bring work to a community than to urge migration. Similarly the handling of payments needs to be done so that it will neither impair self-respect nor overlook hardship for which it has not catered. (c) Work. It is a platitude that few men can lead a satisfying life without work which they feel to be useful. Work is at present also so closely connected with "obtaining a livelihood," that it is doubtful whether a scheme could satisfactorily abolish want without also really abolishing unemployment, or at least incorporating remedies directed specifically at that object. The Beveridge Report admits its dependence on the assumption that there will be maintenance of employment ; but any wise insurance scheme should presume that this main risk will be minimized as far as possible. It is to be considered whether it should include insurance against loss of work as well as against loss of income. Against this contingency it merely offers in addition to the normal employment machinery a training scheme which does not operate till after six months. If there were an ancillary scheme for keeping a pool of employed workers which absorbs immediately all who become unemployed, and from which labour can be drawn to more essential and inelastic industries just as easily as from the ranks of the unemployed, it would have the effect of enhancing individual self-respect, well-being and income, as well as national productive capacity. The nature of the work offered to a man who is temporarily unemployed will chiefly determine whether he wants to undertake it or not. The purely financial incentive, probably acting largely through its effect on prestige, would be that of the difference between benefit rates and the wage offered. Therefore no wage, for healthy adults working full time, should be almost as low as benefit rates, i.e. a minimum wage for any type of work should be fixed at a percentage of the benefit rates. The field of employment is properly adjusted only when it satisfies the following conditions, in the way best suited to the prevailing economic circumstances ; whoever controls industry should ensure this. (1) The work available should be obviously useful and conducted under 292/847/2/174